Governance and Capacity to Manage Resilience of Health Systems: Towards a New Conceptual Framework - Karl Blanchet; Sara L. Nam; Ben Ramalingam; Francisco Pozo-Martin (Kerman University of Medical Sciences, 2017)
The term resilience has dominated the discourse among health systems researchers since 2014 and the onset of the Ebola outbreak in West Africa. There is wide consensus that the global community has to help build more resilient health systems. But do we really know what resilience means, and do we all have the same vision of resilience? The present paper presents a new conceptual framework on governance of resilience based on systems thinking and complexity theories. In this paper, we see resilience of a health system as its capacity to absorb, adapt and transform when exposed to a shock such as a pandemic, natural disaster or armed conflict and still retain the same control over its structure and functions.